Early pH Change Predicts Intensive Care Unit Mortality - Samanta, Sujay (Indian J Crit Care Med, 2018)
AIM OF THE STUDY: Metabolic acidosis is associated with increased mortality in critically ill patients. We hypothesized that early correction of acidosis of presumed metabolic origin results in improved outcomes. PATIENTS AND METHODS: We conducted a prospective, observational study from February 2015 to June 2016 in a 12 bed mixed intensive care unit (ICU) of a 1000 bed tertiary care hospital in the north of India. ICU patients aged above 18 years with an admission pH ≥7.0 to <7.35 of presumed metabolic origin were included. Arterial blood gas parameters including pH, PaO(2), PaCO(2), HCO(3)(−), Na(+), K(+), Cl(−), anion gap (AG), base excess, and lactate at 0, 6, and 24 h along with other standard laboratory investigations were recorded. The primary outcome was to assess the impact of early pH changes on mortality at day 28 of ICU. RESULTS: A total of 104 patients with 60.6% males and 91.3% medical patients were included in the study. Sepsis of lung origin (60.6%) was the predominant etiology. By day 28, 68 (65.4%) patients had died. Median age was 49.5 years, weight 61.7 kg, Sequential Organ Failure Assessment, and Acute Physiologic and Chronic Health Evaluation II scores were 16 and 12, respectively. Nonsurvivors had a higher vasopressor index (P < 0.01), lactate and central venous oxygen saturation (P < 0.05), and lower pH (P < 0.05). A pH correction/change of ≥1.16% during the first 24 h had the best receiver operating characteristic for predicting survival at day 28, with area under the curve (95% confidence interval, 0.72 [0.62–0.82], P < 0.05) compared to HCO(3)(-), BE, lactate, and AG. CONCLUSIONS: Metabolic acidosis is associated with higher mortality in ICU. The rate of change in pH may better predict ICU mortality than other metabolic indices.